An introduction to property law in Australia - Chambers, Robert (Sydney Thomson law book CO., 2008)
The fifth edition of this work remains a succinct, comprehensible and comprehensive statement of Australian real property law. Its basic structure covers the nature of real property, obtaining title to land, land dealings, management and divided ownership and neighbour relations. For this edition, the chapters have been reordered and restructured - possession has considered as part of title to land; public lands have been combined with land rights of indigenous persons; mortgages have been brought within land title; and co-ownership dealt within one chapter. Strata and community title (which can be used for all forms of land use) has been taken from housing to the management chapter, and housing extended to include residential parks and rooming houses. Since the last edition, decisions of Australian courts have considered issues as diverse as priorities of unregistered interests, the loss of easements by abandonment and the scope of settled land powers. A number of national or uniform laws have been enacted for many of the areas at the fringes of real property law. The Australian Consumer Law and national control of consumer credit have increased the court's capacity regarding the regulation of mortgages and to set aside transactions viewed as unfair. There are also uniform laws relating to personal property securities; family property rights for all personal relationships; and even a national water system is promised --
Ch. 1. Concept of real property law -- Ch. 2. Foundational concepts: tenure, possession, estates, trusts and general law priorities -- Ch. 3. Adverse possession -- Ch. 4. The Torrens System and indefeasibility -- Ch. 5. Torrens priorities -- Ch. 6. Public lands and land rights of indigenous peoples -- Ch. 7. Mortgages -- Ch. 8. Dispositions -- Ch. 9. Defeasible transactions -- Ch. 10. Future interests -- Ch. 11. The Rule against perpetuities -- Ch. 12. Co-ownership -- Ch. 13. Management where ownership is divided -- Ch. 14. Landlord and tennant law -- Ch. 15. Housing -- Ch. 16. The Scope and meaning of real property -- Ch. 17. Easements, profits and rentcharges -- Ch. 18. Freehold covenants.
Previous ed.: 2007.
Rev. ed. of: Australian real property law / Adrian J. Bradbrook, Susan V. MacCallum, Anthony P. Moore. 3rd ed. c2002.
Includes bibliographical references and index.
Keywords: Real property -- Australia